Revealing and modulating catalyst reconstruction for highly efficient electrosynthesis of ammonia - Shi, Xinyue; Huang, Wei-Hsiang; Rong, Ju; Xie, Minghui; Wa, Qingbo; Zhang, Ping; Wei, Hainan; Zhou, Huangyu; Yeh, Min-Hsin; Pao, Chih-Wen; Wang, Jie; Hu, Zhiwei; et al. (Nature communications, 2025)
Electrocatalytic nitrate reduction (NO 3 RR) is a promising route for sustainable ammonia synthesis under mild conditions. The widely studied Co-based catalysts undergo significant reconstruction due to nitrate oxidation and electric-field reduction during NO 3 RR, leading to activity degradation. To address this issue, we develop a Co 6 Ni 4 heterostructured catalyst that consists of interlaced metallic Co and Ni domains. Operando X-ray absorption spectroscopy and other in-situ characterization techniques, in conjunction with theoretical calculations, demonstrate that Ni domains function as electron reservoir, which transfer electrons to Co and prevent the accumulation of high-valence Co. Besides, the abundant Co/Ni interfaces also facilitate the NO 3 RR process, thereby achieving a NH 3 Faraday efficiency of 99.21%, a NH 3 yield rate of 93.55 mg h -1 cm -2 , and a NO 3 RR stability of 120 h. Our analyses delve into the underlying causes of the observed stability of metallic Co in Co 6 Ni 4 and provide compelling evidence that the discrepancy between the adsorption quantity of NO 3 - on catalyst surface and the corresponding electron supply is a pivotal factor influencing the reconstruction process. During electrocatalytic nitrate reduction, cobalt-based catalysts degrade fast due to the combined effect of nitrate oxidation and electric-field reduction. Here, the authors develop a Co6Ni4 heterostructured catalyst to prevent high valence Co accumulation and achieve efficient ammonia synthesis.